The challenge of deodorizing post-consumer polypropylene packaging: Screening of the effect of washing, color-sorting and heat exposure - Strangl, Miriam; Lok, Bianca; Breunig, Pascal; Ortner, Eva; Büttner, Andrea (Resources Conservation and Recycling, 2021)
For promoting a sustainable end-of-life-management for plastic packaging, mechanical recycling of especially post-consumer plastic packaging waste constantly gains more attention. To fulfill both industrial and consumer demands, and to increase the recycled content in new applications, high-quality recyclates are of prime importance. However, the odor contamination of post-consumer polyolefin recyclates is not only limiting their application field but is also of concern for the recycling industry and plastic converters since odor emissions during processing might affect the workers’ well-being. As the development of targeted odor reduction strategies requires detailed insights into causative odorants, the present study addresses the odor characterization of different recycled post-consumer polypropylene from the packaging sector by coupling human sensory and comprehensive instrumental analyses. Thereby, the impact of different washing procedures and color sorting were evaluated in terms of their odor reduction potential. In contrast to color sorting, implementation of a hot water washing step led to a noteworthy odor reduction since intensity ratings declined from 7.4 to 4.0, albeit the odor intensity was still not comparable to the low odor level of investigated virgin polypropylene (intensity rating of 2.1). Moreover, a screening on heat-induced emissions of odorous contaminants inspired by a standard extrusion process was performed, revealing a greater emission of odorants in terms of both number and perceived intensities with increasing temperature.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Contaminants; Odor; Olfactometry; Plastic; Polyolefin; Recycling